Natural resources and economic growth : Papers presented at a conference held at Ann Arbor, Michican, April 7-9, 1960 - Spengler, Joseph J.; Resources for the Future; Social Science Research Council (U.S.). (Washington DC : Resources for the Future, Inc., 1961)
This is a proceedings of a conference held at Ann Arbor, Michican, United States of America, April 7-9, 1960 under the joint sponsorship of Resources for the Future, Inc and Committee on Economic Growth of the Social Science Research Council.
Includes bibliographical references.
lje 27/07/2018
Loans
Keywords: Natural resources; Economic development; Economic history